Is the Patent System Sensitive to Incorrect Information? - Freilich, Janet; Kim, Soomi (The Review of Economics and Statistics, 2026)
We investigate whether participants in the patent system are sensitive to information quality by examining how they treat inaccurate information. We use a novel approach to identify patents with inaccurate information: patent-paper pairs where the paper has been retracted and the corresponding patent contains the retracted material. Despite containing inaccurate information, we find that these patents are prosecuted and maintained by many applicants, are not rejected by examiners, and continue to be cited by some downstream readers after retraction. Insensitivity to inaccurate information may lead to erroneous decisions during examination and has implications for patent quality, disclosure, and knowledge flows.